Reconsidering Resentment - De Guzman, Christianne A. (Archīum Ateneo, 2024)
Resentment typically carries a notorious reputation and is often painted as a negative emotion that impedes communal peace, as it traps its victims in the past. The stigma against resentment, conceptualized broadly as a politicized form of anger, can be attributed to the influence of Nietzsche’s notion of ressentiment. Nevertheless, certain forms of resentment are acknowledged by philosophers as valid reactions to legitimate moral infractions. Resentment, they argue, is intrinsically tied to one’s notion of self-respect and moral values. While standard accounts of resentment may be theoretically cogent when applied to singular and individual issues, they are not conceptually adequate to apply to the complexities of collective and structural problems. Focusing on colonial resentment, I argue that resentment ought not to be vilified insofar as it can be a pivotal and instrumentally valuable tool for marginalized people to engage in what Coulthard calls “self-affirmative praxis.” Resentment, as a dual expression of love for oneself and for the other, not only helps colonized subjects avoid the internalization of hatred and violence, but it also helps them detect and aim to fix injustices, as resentment has vital information about justice, fairness, and boundaries.